Conventional methods and emerging technologies for urban river water purification plant: A short review - Mohiyaden H.A.; Sidek L.M.; Ahmed Salih G.H.; Birima A.H.; Basri H.; Mohd Sabri A.F.; Md. Noh M.N. (Asian Research Publishing Network, 2023)
Obviously river water purification procesess are considered as a new approach and their implementation and application are at fundamental basis but there are still current treatment technologies being researched and the outcomes maybe available in a while. This review paper present the various methods for urban river water purification including both conventional methods and new emerging technologies.The review also includes many relevant researches carried out at the laboratory and pilot scales. In river water purification process, biological-advanced technologies and other physicochemical methods are gaining much attention. While previously most treatment of river water have been carried out in conventional direct and bypass treatment, in recent years, here are many emerging technologies can be adapted for river water purification. Until recently, multivariable resources have not been available for researchers to have a rich supplementary data to synthesize and digest since river purification project is new and still in its beginning phase in developing countries. There are still current treatment technologies being researched and the outcomes maybe available in a while. However, the research concluded so far are compiled herein and reported for the first time to acquire a better perspective and insight on the subject with a view of meeting the news approach. Afterward, the most feasible technology could be the combination of advanced biological process (bioreactor systems) including Moving Bed Biofilm Reactor (MBBR) and Integrated Fixed Activated Sludge (IFAS) system, followed by solid separation prior to discharge. 2006-2016 Asian Research Publishing Network (ARPN).